Identification of potential inhibitors of SARS-CoV-2 main protease and spike receptor from 10 important spices through structure-based virtual screening and molecular dynamic study. Issue 2 (26th January 2022) - Sen, Debanjan; Debnath, Pradip; Debnath, Bimal; Bhaumik, Samhita; Debnath, Sudhan
Abstract: The outbreak of novel coronavirus disease (COVID-19) caused by SARS-CoV-2 poses a serious threat to human health and world economic activity. There is no specific drug for the treatment of COVID-19 patients at this moment. Traditionally, people have been using spices like ginger, fenugreek and onion, etc. for the remedy of a common cold. This work identifies the potential inhibitors of the main protease (M pro ) and spike (S) receptor of SARS-CoV-2 from 10 readily available spices. These two proteins, S and M pro, play an important role during the virus entry into the host cell, and replication and transcription processes of the virus, respectively. To identify potential molecules an in-house databank containing 1040 compounds was built-up from the selected spices. Structure-based virtual screening of this databank was performed with two important SARS-CoV-2 proteins using Glide. Top hits resulted from virtual screening (VS) were subjected to molecular docking using AutoDock 4.2 and AutoDock Vina to eliminate false positives. The top six hits against M pro and top five hits against spike receptor subjected to 130 ns molecular dynamic simulation using GROMACS. Finally, the compound 1 -, 2 -, 3 - and 5 -M pro complexes, and compound 17 -, 18 -, 19 -, 20- and 21 - spike receptor complexes showed stability throughout the simulation time. The ADME values also supported the drug-like nature of the selected hits. These nine compounds are available in onion, garlic, ginger, peppermint, chili and fenugreek. All the spices are edible and might be used as home remedies against COVID-19 after proper biological evaluation. Graphical Abstract: UF0001 Communicated by Ramaswamy H. Sarma